Lots of work, poor conditions: Health risks for workers in the German platform economy - Tatiana López; Oguz Alyanak; Patrick Feuerstein; Pablo Aguera (WZB-Mitteilungen: Quartalsheft für Sozialforschung, 2022)
What health risks are workers in the German platform economy exposed to? A new study by the Fairwork project identified three overarching risks: psychological stress due to high levels of job and income insecurity; physical health risks resulting from strenuous working conditions and a lack of appropriate work equipment; and negative effects on workers' well-being linked to experiences of discrimination or harassment.
Keywords: 300